The Effect of STEM on Class X Students' Learning Achievement and Critical Thinking Skills on Environmental Pollution Material - Resti*, Novita; Surakusumah, Wahyu; Sanjaya, Yayan (Universitas Syiah Kuala, 2024)
The success of learning process can be seen from students' achievements and critical thinking skills. One approach that can be used to improve learning achievement and CTS is STEM. Many researchers have conducted research on STEM, but have not been specific about the aspects that play a role on it. This research aims to determine the effect of STEM from the facility aspect, teacher aspect and environmental aspect on learning achievement and CTS. This survey research used purposive sampling involving 152 students. The research instrument consists of a questionnaire to see students' perceptions of STEM from three aspects and a test instrument to determine students' learning achievement and CTS. Data analysis was carried out using partial least square. The research results show that (1) the facility aspect has the greatest influence on learning achievement; (2) environmental aspects have the greatest influence on CTS; (3) the three aspects of STEM learning have a big influence on learning achievement and CTS; and (4) learning achievement greatly influences CTS. These results show that STEM is very feasible to be implemented in the classroom to improve learning achievement and CTS